2017
DOI: 10.1097/md.0000000000006020
|View full text |Cite|
|
Sign up to set email alerts
|

A non-surgical approach to the management of exposure keratitis due to facial palsy by using mini-scleral lenses

Abstract: Rationale:This is a retrospective study aimed to determine the efficacy of mini-scleral contact lens in protecting the cornea and improving vision in cases of facial palsy.Patient concerns:Patients with facial palsy get exposure keratitis because the cornea is dry. They feel pain, discomfort and excessive watering. If left untreated, it leads to permanent damage to the cornea and loss of good functional vision. Mini-scleral lens keep the cornea covered by saline solution all wearing hours.Diagnoses:Three patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 10 publications
1
4
0
1
Order By: Relevance
“…In an important cohort study of 53 eyes in 45 patients with postsurgical lagophthalmos and exposure keratopathy, treatment with a scleral lens was compared to the usual standard of care, and a scleral lens gave rapid, substantial and sustained visual improvement, often from a worse starting point, than eyes in the standard of care group [349]. There are reports of scleral lens use for exposure keratopathy of specific aetiology; thermal injury [350,351], Graves' disease [352], craniofacial trauma [353], acoustic neuroma [354], facial palsy [284,355], post neurosurgery [356] and whilst awaiting eyelid reconstruction [357]. All studies reported that the use of scleral lenses gave positive results based on their outcomes, including improved visual acuity, ocular comfort, and clinical findings.…”
Section: Exposure Keratopathymentioning
confidence: 99%
“…In an important cohort study of 53 eyes in 45 patients with postsurgical lagophthalmos and exposure keratopathy, treatment with a scleral lens was compared to the usual standard of care, and a scleral lens gave rapid, substantial and sustained visual improvement, often from a worse starting point, than eyes in the standard of care group [349]. There are reports of scleral lens use for exposure keratopathy of specific aetiology; thermal injury [350,351], Graves' disease [352], craniofacial trauma [353], acoustic neuroma [354], facial palsy [284,355], post neurosurgery [356] and whilst awaiting eyelid reconstruction [357]. All studies reported that the use of scleral lenses gave positive results based on their outcomes, including improved visual acuity, ocular comfort, and clinical findings.…”
Section: Exposure Keratopathymentioning
confidence: 99%
“…Кератит в случае с двусторонним параличом лицевого нерва исчез в течение одной недели использования склеральных линз. Последующее наблюдение в течение 2 лет показало, что эти пациенты сохранили хорошее зрение без побочных эффектов [35].…”
Section: терапевтическое использование склеральных линзunclassified
“…There are limited references in the peer reviewed literature on the process by which appropriate lens fits are determined. The current literature on scleral lenses consists primarily of case reports or case series, which report indications and outcomes of scleral lens wear [3,[6][7][8] or descriptions of the impact of scleral lenses on anterior ocular structures [5,9,10].…”
Section: Introductionmentioning
confidence: 99%